Field test of Easter lilies transformed with a rice cystatin gene for root lesion nematode resistance - Westerdahl, Becky; Riddle, Lee; Giraud, Deborah; Kamo, Kathryn (Frontiers in Plant Science, 2023)
Easter lilies, Lilium longiflorum cv. Nellie White are a staple of the floral industry. In the U.S. most of the Easter lilies are grown in Oregon and California along the coast where there is a micro climate that is favorable to growth of lilies. The main pest when growing lilies in the field is Pratylenchus penetrans, the root lesion nematode. Easter lilies are one of the most expensive crops to produce because of the cost of chemicals used to control P. penetrans and other pathogens that infect the lilies. Our previous study had shown that transgenic Easter lilies containing a rice cystatin gene (Oc-IΔD86 that has a deleted Asp86) were resistant to P. penetrans in vitro. This study examined growth characteristics of four independently transformed lines of the cystatin Easter lilies compared to non-transformed Nellie White for three seasons in the field in Brookings, Oregon. Liles grown in three soil chemical treatments 1) preplant fumigation, 2) preplant fumigation plus at plant organophosphate, and 3) at plant organophosphate were compared to those grown in nontreated soil. Growth characteristics evaluated included: time of shoot emergence, survival of plants, size of plants, visual ratings of plant health, basal roots and stem roots, weight of foliage and roots, and number and size of bulblets that developed on stems. Nematodes were counted following their extraction from the roots. While not totally resistant, when planted in the field, transformed lines demonstrated and maintained a degree of resistance to lesion nematode over two growing seasons and displayed desirable growth and quality characteristics similar to non-transformed lilies.